Type of injury and recovery time in elite adolescent Korean judo athletes: An epidemiological study - Kim, H.-C.; Park, K.-J. (International Journal of Sports Science & Coaching, 2021)
We aimed to assess the risk of injury associated with training activities in a population of elite adolescent judo athletes, expected to represent South Korea. From 2019, we prospectively collected data on elite adolescent judo athletes at the Korean Training Center. The athletes were assessed by sports medicine doctors, and data were stratified according to sex, weight class, and injury location. We used X² tests to compare groups. Injury rates were expressed as Poisson rates with 95% confidence intervals. One-way analysis of variance was used to investigate the pain score and recovery time due to type of injury. The study included 240 elite adolescent judo athletes whose 617 injuries (annual average, 2.57 injuries/athlete) were recorded. When all athletes were considered, most injuries occurred in the lower extremities (39.71%), followed by the upper extremities (36.63%), trunk (16.69%), and head and neck area (6.97%). Recovery time significantly differed according to the body regions in the weight classes. The pain score and recovery time according to the type of injury were significantly different. When the pain score decreased by 1, the recovery time decreased by about 1.47 days. In all weight classes, female athletes had a higher injury rate than male athletes; both male and female athletes had different recovery time depending on their weight class. The type of injury influenced the pain score and recovery time, with pain score being associated with recovery time.